Comparative Perspectives on Good Governance: Global Principles and Local Realities - Almuqsith, Leda; Taufiqurokhman (Indonesian Scientific Publication, 2025)
Good governance has become an essential pillar of sustainable development, defined through principles such as transparency, accountability, participation, institutional effectiveness, and the rule of law. This narrative review aims to provide a comparative analysis of governance practices across global and local contexts, highlighting both consistencies and divergences in implementation. A systematic literature search was conducted using databases including Scopus, Web of Science, and Google Scholar, with keywords such as “good governance,” “comparative analysis,” “public administration,” and “sustainable development.” Inclusion criteria emphasized studies offering comparative perspectives and empirical or conceptual analyses. Findings indicate that while transparency and accountability foster trust and reduce corruption, public participation remains uneven, influenced by socio-cultural norms and structural inequalities. Institutional effectiveness shows significant variation, with high-performing governance systems in developed countries contrasted by inefficiencies and corruption in weaker systems. The rule of law is critical for integrity and independence, though its entrenchment remains fragile in transitional democracies. Innovations such as e-governance, corporate social responsibility, and environmental, social, and governance frameworks demonstrate potential in enhancing governance outcomes, though their success depends on supportive infrastructure and regulatory consistency. These results underscore that governance is not a static construct but a dynamic process shaped by political, economic, and cultural systems. The review highlights the urgency of strengthening governance frameworks to meet sustainable development goals. Policymakers must adopt adaptive strategies integrating participatory practices, institutional reforms, and technological innovations. Future research should address comparative gaps in developing contexts and further explore cross-sectoral approaches to governance reform.